Distribución y estado de conservación de callicebus oenanthe “mono tocón” en la región San Martín - Tello Alvarado, Julio César (2014)
In 2012 and 2013 a study was conducted to determine the area of distribution and conservation status of Callicehus oenanthe "mono tocon" in the San Martín region. In 2007, the Mono Tocon Project association conducted a similar study that found that C. oenanthe not only lives in the High May, but also in the Low May and in the Central Huallaga. This advance infonnation has been compared with the results obtained during this study. There visited a total of 171 localities in five hydrographic basins of the San Martín region: High May, Under May, Under Huallaga, Huallaga Central and High Huallaga. In each locality infonnation was collected from interviews, vocalizations and observations. In addition to infonnation on agricultura! crops and the threats facing C. oenanthe within its area of distribution. The obtained results show that C. oenanthe he meets in the High May, Under May and Huallaga Central, major presence in the latter basin. 33 % ofthe distribution area ofthe species is occupied by pastures and 37% is affected by the deforestation and the noise pollution.The study shows that C. oenanthe lives in areas below the 1000 m.s.n.m., and occasionally even 1200 m.s.n.m. These areas are frequently destined for different cultures, bringing as consequence the fragmentation ofthe habitat of C. oenanthe. With the present thesis study there provides to itself infonnation about the distribution and condition of conservation of C. oenanthe in the San Martín region, with the purpose of creating conscience and of looking for strategies of conservation as a whole with the local, regional and national governments. The creation of new conservation areas for one of the most endangered species of the worJd is fundamental to ensure the survival of populations. Key words: conservation areas, mono tocon. JR. PROLONGACIÓN 20 DE ABRIL S/N- TELE